Be honest and help me prepare for the future: What people with interstitial lung disease want from education in pulmonary rehabilitation. (May 2015) - Holland, Anne E; Fiore, Julio F; Goh, Nicole; Symons, Karen; Dowman, Leona; Westall, Glen; Hazard, Anita; Glaspole, Ian
Pulmonary rehabilitation (PR) is recommended for people with interstitial lung disease (ILD); however, the educational content of PR was not designed for this group. This study explored the perspectives of patients and ILD clinicians regarding the educational content of PR for ILD. A qualitative study using individual semi-structured interviews was undertaken. Transcripts were coded independently by two investigators and themes established by consensus. Participants were 18 people with ILD (9 idiopathic pulmonary fibrosis, diffusing capacity for carbon monoxide 54 (20)% predicted) and 14 clinicians from 5 countries and 5 disciplines. Major themes from patient interviews were the importance of knowing what the future might bring and the need for honesty from clinicians. Most were happy to attend standard PR education sessions but wanted ILD-specific content. Patients wanted information about end-of-life planning and most were happy to discuss it in a group. Among clinicians, there was no consensus regarding whether prognosis should be discussed in PR. Most clinicians supported discussion of advanced care planning, however, some thought it should not be discussed in a group. We conclude that people with ILD have specific educational needs that may not be met in the current PR format. Patients and clinicians have some discordant views about programme content.